Why do I think and talk about it? Perceived functions and phenomenology of episodic counterfactual thinking compared with remembering and future thinking. Issue 10 (October 2018) - Özbek, Müge; Bohn, Annette; Berntsen, Dorthe
People revisit situations from their past and imagine what could have happened had the situation played out differently. This form of hypothetical thinking is known as episodic counterfactual thinking. The reasons why people engage in episodic counterfactual thinking have not been examined in the same context with remembering the past and imagining the future. We addressed this gap, by focusing on the perceived functions and phenomenological characteristics of the most important episodic counterfactuals compared with episodic memories and future projections in younger adults. We base our analyses on four categories of functions previously identified for past events: reflective, social, generative, and ruminative. The reflective and social functions dominated across all events, with the reflective function being most pronounced for future projections, potentially suggesting a close connection between future projections and self-regulation and/or identity formation. Counter to predictions, the ruminative function was not rated higher for episodic counterfactuals than for other events; however, ratings of ruminative function showed unique correlations with the emotional intensity and involuntary remembering for episodic counterfactuals. Overall, these results suggest that episodic counterfactuals are used for self-reflection and social sharing more than they are used for rumination and generative concerns.